Factors influencing addiction to multiplayer online roleplaying games among adults in the prime working-age group / Shahira Ariffin and Tengku Sharifeleani Ratul Maknu - Ariffin, Shahira; Ratul Maknu, Tengku Sharifeleani (Universiti Teknologi Mara Selangor, 2023)
The trend of remote work has led to a rise in the popularity of multiplayer online games among working adults, offering an escape from their daily routines. The COVID-19 pandemic further boosted the global gaming market, reaching USD 249.55 billion in 2022. This study focuses on Multiplayer Online Role-Playing Games (MORPGs) addiction specifically among working adults, as previous research has mostly centered on younger individuals and students. The paper has investigated the relationships between self-esteem, the need for advancement, emotional states, social motivation, and MORPG addiction. Data was collected from 89 respondents in the Greater Kuala Lumpur/Klang Valley region using convenience sampling. Results indicated that the need for advancement significantly influenced MORPG addiction, while self-esteem, emotional states, and social motivation have no significant impact on addiction among the prime working-age group. In view of the prevalence of MORPGs, the understanding of gamers' behavior in various markets is crucial for games developers' marketing and promotional efforts.